Linear and landscape disturbances alter Mojave desert tortoise movement behavior - Hromada, Steven J.; Esque, Todd C.; Vandergast, Amy G.; Drake, K. Kristina; Chen, Felicia; Gottsacker, Ben; Swart, Jordan; Nussear, Kenneth E. (Frontiers in Ecology and Evolution, 2023)
Describing how animal movements are influenced by landscape features is important to understanding species ecology and how disturbance may alter an individual’s movements, dispersal, and ultimately connectivity among populations. Faster or longer movements adjacent to a localized disturbance or within disturbed areas could indicate reduced habitat quality while slower or shorter movements and reduced movement propensity may indicate higher availability of resources. The Mojave desert tortoise (Gopherus agassizii) is a threatened species that is broadly faced with anthropogenic disturbances within its habitat. We studied tortoise movements using GPS (Global Positioning System) loggers at multiple sites in the Mojave Desert of Nevada and California. Tortoises at our sites encountered localized, linear human infrastructure including paved roads, dirt roads and fences, as well as landscape-scale disturbances (wildfire, off highway vehicle use [OHV], livestock grazing area). We fit two-state (moving and encamped) Hidden Markov models to GPS logger data to infer how tortoise movement behavior relates to anthropogenic and natural features. We found that temporal covariates, individual-level random intercepts, and sex best explained state transition probability in all sites. We compared relationships between tortoise movement and linear disturbances which varied depending on site and context. Tortoises made longer movements within the OHV recreation area, near most dirt roads, and near and a low-traffic paved road, indicating that tortoises avoid these habitat disturbances. Conversely, tortoises made shorter movements in areas of higher slope and near highways suggesting that these features may restrict movement or provide resources that resulted in prolonged use (e.g. forage or drinking locations). Tortoises that encountered fences around utility-scale solar installations were more active and made longer movements near the fences indicative of pacing behavior. These results provide insight into how different disturbances alter tortoise movement behavior and modify tortoise habitat use.